The effect of storytelling on improving pronunciation standards in A1 level students - González Gómez, Nube Beatriz; Campoverde López, Johnny Segundo; Bonilla Tenesaca, Josué Reinaldo (Arandu UTIC, 2025)
Clear communication in English depends on accurate standard pronunciation; incorrect articulation of sounds can lead to misinterpretation, especially in the case of grammatical morphemes such as the third-person singular verb endings -s and -es in the simple present tense. This study investigated the effectiveness of storytelling in teaching English as a foreign language (EFL) to learners at level A1 to determine whether improvements in the pronunciation of these morphemes occurred. The main objective is to examine how storytelling can be implemented to improve the pronunciation of A1 students. Twelve students from a public school in Azogues, Ecuador, aged twelve to fourteen, participated in this research. The investigation employed various tools, such as a pronunciation pretest and posttest, an observation checklist, and an online survey to gather both qualitative and quantitative data. Students engaged in storytelling activities, emphasizing verbs with the endings -s and -es incorporated into regular classes. Students who exhibited greater pronunciation accuracy and motivation contributed to revealing significant improvements in the precise production of target sounds. Future research should explore how storytelling influences pronunciation retention over extended periods and its relationship to other phonological elements.